A feasibility study on the development of a videogame collection in the CIIT library in support of game design and development courses - Udasco, Alvin B. (School of Library and Information Studies, University of the Philippines Diliman, 2015)
There have been numerous studies relating video games to education and learning. In countries like the United States of America, libraries have started including video games in their collection. This study aimed to introduce the concept of a videogame collection in a Philippine library to support the field of game design and development by determining the feasibility of developing a videogame collection in the CIIT library through three aspects: market, technical and financial; and using a SWOT analysis.